Pasteurella multocida infective endocarditis: a case report. - V. Thamlikitkul (2018)
A 17-year-old man presented with acute febrile illness with jaundice, embolic skin lesion, heart murmur, renal insufficiency and abnormal CSF. Pasteurella multocida was isolated from blood cultures. In spite of adequate antibiotic treatment for endocarditis of the mitral valve, he developed a fatal ruptured cerebral mycotic aneurysm. Post mortem examination revealed an atrial septal defect, vegetation at the anterior mitral leaflet, intraventricular, subarachnoid and intracerebral hemorrhage.